CT-Guided Screw Fixation of Vertical Sacral Fractures in Local Anaesthesia Using a Standard CT - Reuther, G.; Röhner, U.; Will, T.; Dehne, I.; Petereit, U. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To evaluate time efficiency, radiation dose, precision and complications of percutaneous iliosacral screw placement under CT-guidance in local anaesthesia.Material and Methods: Retrospective analysis of 143 interventions in 135 patients during a period of 42 months. Implant failures could be evaluated in 85/182 screws and bony healing or refracturing in 46/182 screws.Results: A total of 182 iliosacral screw placements in 179 vertical sacral fractures (105 unilateral, 37 bilateral) took place in 135 patients. 166/179 of the sacral fractures were detected in Denis zone 1, 10 in Denis zone 2 and 3 in Denis zone 3. No screw misplacements including the simultaneous bilateral procedures were noted. The average time for a unilateral screw placement was 23 minutes (range: 14 – 52 minutes) and 35 minutes (range: 21 – 60 minutes) for simultaneous bilateral screwing. The dose length product was 365 mGy × cm (range: 162 – 1014 mGy × cm) for the unilateral and 470mGy × cm (range: 270 – 1271 mGy × cm) for the bilateral procedure. 1 gluteal bleeding occurred as the only acute minor complication (0.7 %). Fracture healing was verified with follow-up CTs in 42/46 sacral fractures after screw placement. Backing out occurred in 12/85 screws between 6 and 69 days after intervention. In 8 patients contralateral stress fractures were detected after unilateral screw placement between day 10 and 127 (average: 48 days).Conclusion: CT-guided iliosacral screw placement in sacral fractures is a safe tool providing a very high precision. The radiation dose is in the order of a diagnostic CT of the pelvis for both unilateral and bilateral screws. Contralateral stress fractures in unilateral screw placements have to be considered during the first weeks after intervention.Key Points:• Sacral fractures are frequent in the elderly and are often only detected in CT or MRI.• CT-guided screw placement is a precise and time-efficient procedure in non-dislocated vertical fractures of the sacral wings.• Contralateral stress fractures may occur after unilateral screw placements.Citation Format:• Reuther G, Röhner U, Will T et al. CT-Guided Screw Fixation of Vertical Sacral Fractures in Local Anaesthesia Using a Standard CT . Fortschr Röntgenstr 2014; 186: 1 – 6
Keywords: bones; pelvis; skeletal-axial; CT; interventional procedures; percutaneous